THEORETICAL AND LEGAL ANALYSIS OF THE DEFINITIONS “RIGHT OF THE NATIONS” AND “RIGHT OF THE PEOPLE” ON THE SELF- DETERMINATION - Zaure Karimovna Аюпова; Daurenbek Umirbekovich Кусаинов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
In this article the theoretical and legal analysis of the concepts of “nation”, “people” was held, and reveals the meaning and content of the problems of self-determination of nations, as well as the peculiarities of the legal supplement of the rights and freedoms in a multi-ethnic state. Besides, the authors show some directions and the situation of this problem in the international community at the present stage of the development of ethnic groups.